AGREEMENT BETWEEN DIFFERENT TYPES OF BLOOD PRESSURE MONITORING: A SYSTEMATIC REVIEW AND NETWORK META-ANALYSIS. (June 2022) - Yeh, Jiunn-Tyng; Lee, Chun-Wei; Chen, Yu-Jen; Huang, Shao-Li; Wang, Wei-Ting; Huang, Chi-Jung; Chiu, Tzu-Jung; Chen, Chen-Huan; Chiang, Chern-En; Cheng, Hao-Min
Abstract : Objective: An accurate blood pressure measurement (BPM) is important for diagnosing and managing hypertension. Several monitoring techniques of BPM, including office BPM (OBPM), ambulatory BPM (ABPM), and home BPM (HBPM) have been widely utilized; however, the corresponding agreement and conversion between these modalities remained elusive. With emerging evidence suggesting the utility of out-of-office blood pressure (BP) for hypertension management, an investigation into the relationship between BPMs is crucial. Therefore, we performed a systematic review and network meta-analysis from published studies and compared the reported BP values between different BPM modalities. Design and method: We searched MEDLINE and Scopus for observational studies and andomised controlled trials reporting more than one type of BPM by Apr 6, 2021. Studies with participants that were over 18 years old and received at least two different BPM within a week were included. The risk of bias of included studies was assessed by the quality of the study and BPM techniques. We calculated the mean differences (MD) between modalities and pooled the measurements using random-effects network meta-analysis. Furthermore, the agreement between BPMs within different BP levels was investigated using network meta-regression. Results: We identified 10970 studies and included 486/482 studies (467654/466167 individuals) for SBP/DBP measurements. With reference to OBPM, the MDs of SBP of casual OBPM, HBPM, 24 hours ABPM, daytime ABPM, and night time ABPM, were 2.8, -5.5, -10.0, -6.4, -19.5mmHg, respectively. For DBP the MDs were 1.3, -3.0, -6.3, -3.19, and -13.76mmHg. Network meta-regression (see figure) showed that the MDs between OBPM and casual OBPM were rather fixed; however, those between OBPM/HBPM or OBPM/ABPM followed a negatively associated linear relationship across BP levels. The diagnostic thresholds of different BPMs corresponding to OBPM 140/90mmHg and 130/80mmHg were generally in agreement with current guidelines. Conclusions: Our study demonstrated the agreement between common BPM modalities by synthesizing the body of evidence from a comprehensive search. Furthermore, the regression model showed that the MDs of measurements between modalities may vary depending on the mean BP. Our systematic review supports the diagnostic thresholds for different BPM recommended by current guidelines.